2006
DOI: 10.1038/ja.2006.28
|View full text |Cite
|
Sign up to set email alerts
|

Pterocidin, a Cytotoxic Compound from the Endophytic Streptomyces hygroscopicus

Abstract: A new cytotoxic compound, pterocidin, was isolated from the endophytic Streptomyces hygroscopicus TP-A0451, and the structure was determined on the basis of spectroscopic data. Pterocidin showed cytotoxicity against some human cancer cell lines with IC 50 values of 2.9ϳ7.1 mM. [6] and its derivatives, and herbimycins [7] and their hydroquinone congeners. Our continuous search for bioactive compounds from the strain TP-A0451 led to the isolation of pterocidin (1), a new cytotoxic compound. We herein describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 17 publications
0
22
0
2
Order By: Relevance
“…IR spectrum was measured on a Perkin Elmer Spectrum 100 (Perkin-Elmer, Fremont, CA, USA). NMR spectra were obtained on a Bruker AVANCE 400 or a Bruker AVANCE 500 spectrometer (Bruker, Rheinstetten, Germany) in DMSO-d 6 , referenced to residual solvent signals (d 2.49 for 1 H; d 39.5 for 13 C). HR-ESI-TOF-MS was recorded on a Bruker microTOF focus.…”
Section: Experimental Procedures General Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectrum was measured on a Perkin Elmer Spectrum 100 (Perkin-Elmer, Fremont, CA, USA). NMR spectra were obtained on a Bruker AVANCE 400 or a Bruker AVANCE 500 spectrometer (Bruker, Rheinstetten, Germany) in DMSO-d 6 , referenced to residual solvent signals (d 2.49 for 1 H; d 39.5 for 13 C). HR-ESI-TOF-MS was recorded on a Bruker microTOF focus.…”
Section: Experimental Procedures General Experimental Proceduresmentioning
confidence: 99%
“…2 Meanwhile, it is quite notable that further discovery of unknown metabolites from Streptomyces is predicted by the genome analysis: the number of metabolites actually isolated is far more below the number of secondary metabolite biosynthetic gene clusters identified in the whole genomes of S. avermitilis and S. coelicolor. 3,4 As a part of our chemical investigation on microbial secondary metabolites, we reported plant-growth promoting spiroacetals of polyketide origin, 5 a linear polyketide with a dlactone terminus with cytotoxic activity, 6 a polycyclic tetronate with antiinvasive activity 7 and a biosynthetically unprecedented heterocyclic polyketide with antibacterial and antiinvasive activities 8 from Streptomyces. During the course of our continuing effort to discover structurally unique secondary metabolites from these organisms, a new modified peptide was isolated from the culture broth of a soilderived actinomycete strain Streptomyces sp.…”
mentioning
confidence: 99%
“…Streptomyces hygroscopicus is a species which produces a variety of antibiotics belonging to different classes with distinct structure and possessing certain biological properties [5,7,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Igarashi et al, 2006;Yamada et al, 2012) or produced milbemycin oxime, which was shown to be toxic to mice (Xu et al, 2010).…”
Section: Minireview 3 Evaluating Genetic Stability Of Microorganismsmentioning
confidence: 99%